The efficiency of using the technology of “edutainment” in teaching foreign languages - Julia D. Ermakova; Tamara M. Nosova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Modern tendencies to general digitalization in all spheres of life in our society create objective preconditions to pay teachers’attention to the new approach, constructing the educational process which has arisen recently - edutainment (from Eng. “education” and “entertainment”). The peculiarity of edutainment technology is in introduction modern forms of entertainment in the system of traditional lectures, lessons, classes, seminars and master classes, as without television programs, desktop, computer and video games, movies, music, websites, multimedia programs it is difficult to imagine the daily reality of any student. The rapidly developing innovative developments in the field of technology within last ten years gave teachers and students the opportunity to widely use all kinds ofmultimedia resources for the most effective learning of a foreign language, providing immersion in the "real" language environment. Edutainment offers resources that can be used in almost any field of teaching, and in learning a foreign language, probably even more efficiently than anywhere else. In addition to the obvious advantages of using the technology of edutainment, this article examines the effectiveness of using this kind of multimedia forstudents’ professional language skills development in comparison with traditional methods. The results of the experimental part confirmed the feasibility of using interactive resources as components of edutainment, combining them with proven classical, academic approaches to teaching foreign languages, as well as a number of shortcomings that were identified, on the basis of which warnings were formulated regarding the use of the edutainment approach to higher education in general and foreign language teaching in particular.